Perceived Stress and Its Relationship to Moral Resilience Among Nurses in the Hail Region, Saudi Arabia - Albaqawi, Hamdan; Alrashidi, Maha Sanat (Makara Journal of Health Research, 2022)
Background: This study aimed to determine the relationship between perceived stress and moral resilience among nurses. Methods: The researcher used a quantitative–comparative correlational study design that utilized a self-administered questionnaire with 393 nurse participants in the Hail Region, Saudi Arabia. Adapted questionnaires were distributed through Google Form survey. Data collection was conducted between October and November 2021. Results: The nurses were moderately stressed (21.69/30) but morally resilient (2.74/4). Perceived stress scale (p < 0.033) and moral resilience (p < 0.25) were found to be significantly associated with gender. The designated ward and age were not significantly associated with perceived stress and moral resilience. Conversely, the years of experience showed a significant association with perceived stress (p < 0.038) but not with moral resilience (p > 0.255). Finally, no relationship was observed between perceived stress and moral resilience (p > 0.248). Conclusions: The nurses were perceived to be moderately stressed but morally resilient. Gender was found to have a significant association with perceived stress and moral resilience but not with designated ward and age. Conversely, the years of experience had a significant association with perceived stress but not with moral resilience. Meanwhile, perceived stress had no significant relationship with moral resilience. Therefore, being morally robust allows nurses to respond to challenging, frequently intractable ethical issues that arise in clinical practice and during pandemics, regardless of the underlying stress at work.